Eye tracking technology in sports-related concussion: a systematic review and meta-analysis. (20th December 2018) - Snegireva, N; Derman, W; Patricios, J; Welman, K E
Abstract: Objective : The development of objective quantitative tools for the assessment and monitoring of sports-related concussion is critical. Eye tracking is a novel tool that may provide suitable metrics. The aim of this review was to appraise current evidence for the use of eye tracking technology in sports-related concussion assessment and monitoring. Approach : A systematic literature review was conducted following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. A search was run using Google Scholar, Microsoft Academic and PubMed for literature published between January 1980 and May 2018. Included were empirical research studies in English where at least 50% of the research participants were athletes, the participants were individuals with a diagnosis of concussion, and eye movements were measured using an eye tracking device. Main results : This systematic review integrates 21 publications on sports-related concussion and eye tracking technology, nine of which also qualified for the meta-analysis. Overall, the literature reported significant findings for variables in each of the four classes of eye tracking measurements (movement, position, count, and latency). Meta-comparison was made for seven variables for the acute concussions (the difference between the concussed and the control groups was significant for all of them) and one variable for the latent concussions (the difference was not significant). Significance : Most saccadic and pursuit deficits may be missed during clinical examination, and therefore eye tracking technology may be a useful and sensitive screening and monitoring tool for sports-related concussions. The inconsistencies between the eye movement metrics and methodology still make inferences challenging; however, using tasks that are closely related to brain areas involved in executive functions (such as memory-based saccade or antisaccade tasks) in the acute injury phase holds promise in differentiating between athletes who have a concussion compared to those who do not.